2013
DOI: 10.1122/1.4767982
|View full text |Cite
|
Sign up to set email alerts
|

Transient overshoot extensional rheology of long-chain branched polyethylenes: Experimental and numerical comparisons between filament stretching and cross-slot flow

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 66 publications
(79 reference statements)
0
31
0
Order By: Relevance
“…We believe the stress measured by the EVF is too low, especially at low strain rates, which was also observed by Hoyle et al [12] where the filament stretching measurements were compared with the Sentmanat elongational rheometer measurements. Thus forǫ = 0.01s −1 in Figure 3(b) , there is deviation already from ǫ = 0.5, while forǫ = 2.5s −1 , the EVF measurement agrees with the DTU-FSR measurement up to ǫ = 3.5.…”
Section: Startup and Steady-state Extensional Flowmentioning
confidence: 78%
See 2 more Smart Citations
“…We believe the stress measured by the EVF is too low, especially at low strain rates, which was also observed by Hoyle et al [12] where the filament stretching measurements were compared with the Sentmanat elongational rheometer measurements. Thus forǫ = 0.01s −1 in Figure 3(b) , there is deviation already from ǫ = 0.5, while forǫ = 2.5s −1 , the EVF measurement agrees with the DTU-FSR measurement up to ǫ = 3.5.…”
Section: Startup and Steady-state Extensional Flowmentioning
confidence: 78%
“…A maximum in the transient extensional stress of LDPE was observed by several groups [8,9,10]. Steady stress following the stress overshoot was reported firstly by Rasmussen et al [11] and has been experimentally confirmed by comparing the measurements from the filament stretching rheometer and the cross-slot extensional rheometer [12], as well as by comparing the constant stretch rate and constant stress (creep) experiments [13]. Several models have been developed [12,14,15] for the attempt to understand the physics behind the stress overshoot.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Finally, we note that recent experiments on branched polyethylene resins have indicated that there may be stress overshoots prior to the steady state in extensional flow [Wagner and Rol on-Garrido (2008); Alvarez et al (2013); Hoyle et al (2013)], though others dispute these findings [M€ unstedt and Star y (2013)]. To date, a detailed molecular explanation of the stress overshoots appears to be lacking [for example, the model in Hoyle et al (2013) is phenomenological].…”
Section: Discussionmentioning
confidence: 99%
“…To date, a detailed molecular explanation of the stress overshoots appears to be lacking [for example, the model in Hoyle et al (2013) is phenomenological]. In this work, our focus has been on developing nonlinear rheology predictions based on molecular structure.…”
Section: Discussionmentioning
confidence: 99%